Molecular composition and expression pattern of the extracellular matrix in a mossy fiber-generating precerebellar nucleus of rat, the prepositus hypoglossi. (6th May 2015) - Gaál, Botond; Kecskes, Szilvia; Matesz, Clara; Birinyi, Andras; Hunyadi, Andrea; Rácz, Éva
Highlights: Extracellular matrix appears in condensed and diffuse forms in the rat prepositus hypoglossi nucleus. Perineuronal nets and axonal coats are mostly present in magnocellular part of prepositus hypoglossi nucleus. Perineuronal nets showed most intense staining for aggrecan and tenascin-R. Extracellular matrix shows area-dependent distribution in the prepositus hypoglossi nucleus. Abstract: The prepositus hypoglossi nucleus (PHN) is a mossy fiber-generating precerebellar nucleus of the brainstem, regarded as one of the neural integrators of the vestibulo-ocular reflex. The aim of the present work is to reveal the distribution of various molecular components of the extracellular matrix (ECM) in the prepositus hypoglossi nucleus by using histochemical and immunohistochemical methods. Our most characteristic finding was the accumulation of the ECM as perineuronal net (PNN) and axonal coat and we detected conspicuous differences between the magnocellular (PHNm) and parvocellular (PHNp) divisions of the PHN. PNNs were well developed in the PHNm, whereas the pericellular positivity was almost absent in the PHNp, here a diffuse ECM was observed. In the PHNm the perineuronal net explored the most intense staining with the aggrecan, and tenascin-R antibodies followed by the hyaluronan, then least with reactions for chondroitin sulfate-based proteoglycan components and HAPLN1 link protein reactions, but PNNs were not observed with the versican, neurocan, and brevican staining. We hypothesized that the difference in the ECM organization of the two subnuclei is associated with their different connections, cytoarchitecture, physiological properties and with their different functions in the vestibular system.